Vulnerability Assessment of Lakes on the Degradation in Barlinecko-Gorzowski Landscape Park - Daniszewski, Piotr (Asian Journal of Chemistry, 2013)
The purpose of the work was to determine the impact of use on the evolution of water quality in lakes basin covered by tests. The studies covered seven tanks along with their drainage basins (the direct and total) Barlinecko-Gorzowski landscape located in the Park. In order to determine the impact of the estimated load of nitrogen and phosphorus compounds, reaching into the lake from the direct catchment area (as rafting area) and the total (as the supply of courses). Received loads of phosphorus were compared with the limit and dangerous cargoes for the test tanks. The work was also assessed and the impact of the natural resistance of the water catchment area of the lakes in the degradation the pace of delivery to them.